H.Yusuf Haris' Leadership Strategy in Building Muhammadiyah Sintang (1963-1987) - Ahmad Fathi Farhat; Zuhrotul Latifah (UNIVERSITAS MUHAMMADIYAH METRO, 2027)
This study examines the strategic role of H. Yusuf Haris in the development of Muhammadiyah in Sintang during the period 1963-1987. This study uses a historical method with a biographical-sociological approach through the stages of heuristics, verification, interpretation, and historiography.Â This study reveals that H. Yusuf Haris played a key role in building the foundation of the Muhammadiyah Sintang organization through institutional consolidation, establishing inclusive schools, and developing Muhammadiyah charitable enterprises, and the implementation of adaptive da’wah strategies in line with the conditions of a multicultural society.Â The findings show that Muhammadiyah's success in Sintang did not solely depend on the structural support of the central organization, but rather on the ability of local leaders to read socio-political dynamics and formulate adaptive strategies. The contribution of this study lies in enriching local historiography and understanding the dynamics of the modern Islamic movement in the interior of West Kalimantan.